2019
DOI: 10.1175/mwr-d-19-0019.1
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Parametric Sensitivity for Wind Ramp Events in the Columbia River Basin

Abstract: This work investigates the sensitivity of wind speed forecasts during wind ramp events to parameters within a numerical weather prediction model boundary layer physics scheme. In a novel way, it explores how these sensitivities vary across 1) ensemble members with different initial conditions, 2) different times during the events, 3) different types of ramp-causing events, and 4) different horizontal grid spacing. Previous research finds that a small number of parameters in the surface layer and boundary layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The elevation of the CRG is very near sea level, compared to the Cascade passes, whose lowest elevation is 900 m (Sharp and Mass, 2004). Thus, the CRG serves as a primary pathway for the intrusion flows into the basin (Smith and Ancell, 2019). Observational studies show that flows frequently originate west of the Cascade ranges, propagate through the CRG (Banta et al, 2020), and move eastward through the basin (Brewer and Mass, 2014).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…The elevation of the CRG is very near sea level, compared to the Cascade passes, whose lowest elevation is 900 m (Sharp and Mass, 2004). Thus, the CRG serves as a primary pathway for the intrusion flows into the basin (Smith and Ancell, 2019). Observational studies show that flows frequently originate west of the Cascade ranges, propagate through the CRG (Banta et al, 2020), and move eastward through the basin (Brewer and Mass, 2014).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…They found that the perturbation of IC produced a larger ensemble spread than application of different PBL schemes, indicating that changes (errors) in IC can lead to large uncertainties in wind flow forecasts. Smith and Ancell (2019) further reported considerable differences in the results of parametric sensitivity among the ensembles started from different ICs. By characterizing NWP model forecasting errors using doppler-lidar measurements over the Columbia River Basin, Banta et al (2020) suggested that the forecasting errors could be imported from upstream or generated locally at an earlier time, which emphasized the impacts of both local thermal gradient and large-scale circulation initial status on wind forecast.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the composite analyses and cross-section (Sharp and Mass, 2004). Thus, the CRG serves as a primary pathway for the intrusion flows into the basin (Smith and Ancell, 2019). Observational studies show that flows frequently originate west of the Cascade ranges, propagate through the CRG (Banta et al, 2020), and move eastward through the basin (Brewer and Mass, 2014).…”
Section: Discussion and Summarymentioning
confidence: 99%